A model of teachers’ growth mindset, teaching enjoyment, work engagement, and teacher grit among EFL teachers - Liu, Li; Fathi, Jalil; Allahveysi, Seyyed Pedram; Kamran, Kimia (Frontiers in Psychology, 2023)
Because of the importance of positive emotions in second language (L2) acquisition, researchers have undertaken studies to investigate L2 learners’ emotions. Nevertheless, L2 teachers’ emotions still require more scholarly attention. Against this backdrop, we sought to test a model of teachers’ growth mindset, teaching enjoyment, work engagement, and teacher grit among English as a foreign language (EFL) teachers. To this end, 486 Chinese EFL teachers volunteered to partake in an online survey and completed the questionnaires of the four constructs in question. Confirmatory factor analysis was performed to ensure the construct validity of the used scales. Then structural equation modeling (SEM) was used to test the hypothesized model. SEM results indicated that teaching enjoyment, teacher grit, and growth mindset directly predicted EFL teachers’ work engagement. In addition, teaching enjoyment affected work engagement indirectly via the mediation of teacher grit. Likewise, teacher grit mediated the effect of growth mindset on teachers’ work engagement. Finally, the implications of these findings are discussed.